Colour of inland and coastal waters : a methodology for its interpretation - Pozdnjakov, Dmitrij Viktorovič (Springer, 2003)
Sadržaj: 1. Basic notions and relationships ; 2. Optical properties of non-Case I waters: hydro-optical models ; 3. Colour formation in natural waters: numerical simulations of the forward ; 4. Quantitative interpretation of satellite colour images over non-Case I waters: numerical simulations of the inverse problems ; 5. Retrieval of water quality distributions from SeaWiFS images over non-Case I waters